07 The approach to generate oncolytic adenovirus by sirna mediated e1b silencing. (5th December 2017) - Zhang, XN; Matskova, L; Zheng, BY; Ernberg, I; He, Z; Huang, ZN
Abstract : Background: Adenovirus is a gene transfer vehicle used in anticancer biotherapy. Oncolytic adenoviruses are prepared so that the recombinant viruses possess more potent cytotoxicity to target cells. E1B is an anti-apoptotic protein encoded by adenovirus. In the present study we tested whether the potential antitumor activity of BLU recombinant adenovirus of tumour suppressor BLU could be enhanced by silencing E1B with siRNA. Methods: The shuttle plasmid of BLU was constructed as described, and was assembled to be recombinant adenovirus. siRNAs against adenoviral E1B were designed by locating oligo?nucleotides downstream of AA dinucleotides within the genomic DNA sequence and chemically synthesised. Their ability to silence the expression of E1B was tested by transfection and anti-E1B Western blotting. The potential of BLU to inhibit in vitro and in vivo tumour cell growth was compared between siRNA transfected cells and controls. Results: Up to 6 strains of siRNAs were designed and synthesised. They silenced the expression of E1B to different extents, and remarkably reduced the cell viability and formation of xenograted tumours in nude mice. Conclusion: In addition to knockout of the E1B coding cassette, siRNA mediated E1B also serves as an approach to prepare oncolytic adenovirus. Acknowledgements: Supported by grants from UICC (ICRETT Fellowship), Guangdong Commission of Health and Family Plan (Grant No. 2014A276).